Gender Construction in Indonesian Language Textbooks for Junior High School: A Sara Mills Discourse Analysis Approach - Imas Komala; Jeremi Tombi Layuk Tulak; Widyatmike Gede Mulawarman; Yusak Hudiyono (Side: Scientific Development Journal, 2025)
This study aims to reveal how gender construction is represented in Indonesian language textbooks at the junior high school level, using Sara Mills' critical discourse analysis approach. This method emphasizes the positioning of subjects(the party who holds the power to observe, evaluate, or describe) and objects(the party who is observed, evaluated, or described) within discourse and the power relations shaped through language. The analysis focuses on narratives, dialogues, and character representations in nationally used textbooks. The findings show a persistent gender bias, including male-dominated representation, stereotypical portrayals of female roles, and the positioning of female characters as narrative objects. These results suggest that textbooks continue to reproduce patriarchal social structures, despite some efforts to present gender equality. The study recommends curriculum revision and textbook author training to enhance sensitivity to gender equality issues. The method used in this study is qualitative, employing a critical discourse analysis approach.